PERAN MODAL SOSIAL PADA LEMBAGA PEMASARAN SAPI POTONG DI KECAMATAN BANTIMURUNG KABUPATEN MAROS - Riska Eldiana; Syahdar Baba; Agustina Abdullah (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. This study aims to determine how the role of social capital at marketing agencies of beef cattle in the District Bantimurung Maros. This type of research is quantitative descriptive by using quantitative and qualitative data, which was held from March to April 2015 on beef cattle marketing agencies in the District Bantimurung Maros. Analysis of the data used in this study descriptive statistics, while to determine the role of social capital on marketing agencies using Likert scale. Results of this study indicate that the role of social capital on beef cattle marketing agencies in the District Bantimurung Maros at the high category (1206.4 to 1551) with a total overall weight is 1233. if you see the  magnitude of the score or the weight obtained based marketing agency response cow cut to social capital, it can be said that are in the High category. On Social Capital variables have weights 318 norm with medium category, the network has a weight of 240 with the medium category, the trust has a weight of 352 with a high category, has a weight of 323 reciprosity the medium category.